Between sentences - Thesen, Jo-Ann (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
My stories explore different forms, including flash fiction. Some use the fairy tale form to combine fiction and non-fiction in order to reach the essence of the story. In this I am influenced by Kate Bernheimer, who speaks of the "flatness, abstraction, intuitive logic and normalized magic" of traditional fairy tales. A number of stories are set in the places I worked as a newspaper reporter. Here I use my old press reports as starting points for the real or imagined story behind the news "“ often involving miscommunication, dominance, exploitation, the tension between isolation and belonging, and the nuances of family relationships.
Keywords: Uncatalogued